The Role of Government Initiatives in Supporting Education and Health Issues in the Arab World Study in Egypt and Saudi Arabia (American Journal of Education and Technology, 2024)
The study has given a comprehensive analysis of government initiatives in education and health sectors in Saudia Arabia and Egypt, aiming to assess their impact on diverse demographic groups. The data shows key demographic statistics, perceptions of initiative effectiveness, and communication strategies employed. Findings suggested that the government initiatives have positively created an impact on education, particularly in supporting children’s rights and addressing child-related concerns, while early detection and treatment for chronic diseases demonstrate holistic well-being. The study highlights the importance of communication channels like social media in raising awareness and promoting citizen engagement. It has been recommended that their strategies be enhanced in terms of tailoring the initiatives to specific demographics and continuous improvement for successful government initiatives in both countries.